Dead voices and lost sounds: an imagined sonic history - Kapstein, Adrienne (Revista Vórtex, 2021)
A project description of a sound art installation and interactive performance presented as part of the Up Close Festival in New York City in the winter of 2019/2020. The article is authored by the creator and director of the piece, Adrienne Kapstein. Created for an all-age audience, the piece was a unique, relational and socially engaged experience that merged sound art, live performance, illusion, technology, and audience participation. Designed to be completed in partnership with members of the community it sought to serve, the piece invited participation from every audience member through multiple and varied means of engagement. Link: https://youtube.com/playlist?list=PLXdYuKtwUhUrirWQ0B2X7XhfrBCGJVlGn